Menguak Hadis Palsu yang Masyhur: Upaya Autentifikasi Sabda Nabi - Bustamin Bustamin (Refleksi: Jurnal Kajian Agama dan Filsafat, 2005)
So far, hadith has been a theological reference to strengthen religious behavior. It is often used as motivation to foster religious enthusiasm related to the social dimension. From there emerge hadiths that are so familiar to the ears of Muslims, as they are often conveyed and directly related to social issues. However, the fame of a hadith often closes our concern to critically assess the status of the hadith. This paper attempts to critically examine the highly popular hadiths in society to see the extent of their authenticity. All of this needs to be done as an effort to place the hadith clearly and authentically and to distinguish between the words and the chain of words.